Mitchell and Golden metatarsal osteotomies for the treatment of moderate hallux valgus deformity: A comparative analysis - Mikić, Nadan; Grujoska-Veta, Dušanka; Čobeljić, Goran; Gavankapetanović, Ismet; Vukašinović, Zoran; Soldatović, Ivan; Popović, Miroslava (Vojnosanitetski pregled, 2021)
Background/Aim. Despite bunion surgery having been performed for more than 100 years, there has yet to be a technique considered as the “Gold Standard”. The aim of the study was to compare postoperative results of Mitchell vs. Golden methods of treating moderate hallux valgus deformity. Methods.This observational case control study included 49 patients (81 feet) who had the Mitchell distal metatarsal osteotomy performed, and 49 patients (77 feet) that had the Golden proximal metatarsal osteotomy performed. The results of treatment were evaluated using Hellal’s modification of the Bonney and McNab classification and the Hallux Metatarsophalangeal Interphalangeal Score (HMIS). The statistical analysis of the results was done, thus the values p < 0.05 were considered statistically significant. Results. Both operative procedures showed successful and statistically significant postoperative results compared to the preoperative status (p < 0.001). Comparative analysis of the results from the Mitchell and Golden procedures, according to the Hellal’s modification of Bonney and McNab classification, proved that there was a high statistically significant difference in favor of the Mitchell method (p < 0.001), whereas the comparison based on the HMIS showed no statistically significant difference (p = 0.123) between the two methods. The estimated results analysis of both procedures, based on the values of hallux valgus angle, intermetatarsal angle, sesamoid position, length of immobilization, treatment duration and complications demonstrated that there was a highly significant difference in favor of the Mitchell method (p < 0.001), whereas the value of the shortening of the first metatarsal bone indicated that the shortening was greater in the Mitchell method (p < 0.001), which goes in favor of the Golden method. Regarding the flexion of the thumb of the feet operated on, there was no statistically significant difference (p = 0.723). Conclusion. The examinations performed indicated that both methods showed good postoperative results, but applying the Mitchell method they were better.
Keywords: hallux valgus; osteotomy; surgical procedures, operative; treatment outcome.